Brain serotonin transporter binding in former users of MDMA ('ecstasy'). - Selvaraj, S; Hoshi, R; Bhagwagar, Z; Murthy, N; Hinz, R; Cowen, P; Curran, H; Grasby, P (2009)
BACKGROUND: Animal experimental studies have prompted concerns that widespread use of 3,4-methylenedioxymethamphetamine (MDMA; 'ecstasy') by young people may pose a major public health problem in terms of persistent serotonin neurotoxicity. AIMS: To determine the status of brain serotonin neurons in a group of abstinent MDMA users. METHOD: We assessed the integrity of brain serotonin neurons by measuring serotonin transporter (SERT) binding using positron emission tomography (PET) and [(11)C]DASB in 12 former MDMA users, 9 polydrug users who had never taken MDMA and 19 controls who reported no history of illicit drug use. RESULTS: There was no significant difference in the binding potential of [(11)C]DASB between the groups in any of the brain regions examined. CONCLUSIONS: To the extent that [(11)C]DASB binding provides an index of the integrity of serotonin neurons, our findings suggest that MDMA use may not result in long-term damage to serotonin neurons when used recreationally in humans.